Saliva-acquired pellicle inspired multifunctional gargle with wet adhesion, photodynamic antimicrobial, and In situ remineralization properties for dental caries prevention - Jiayi Shi; Xuekai Qi; Ying Ran; Qiang Zhou; Yiqin Ding; Lujian Li; Youyun Zeng; Dongchao Qiu; Zhibin Cai; Xiaojun Cai; Yihuai Pan (Bioactive Materials)
Dental caries is primarily caused by cariogenic bacteria metabolizing carbohydrates to produce acidic substances that erode the dental hard tissues. Traditional remineralization treatments often have limited efficacy due to their lack of antibacterial activity. According to the Interrupting Dental Caries (IDC) theory, ideal caries-preventive materials should possess both antibacterial and remineralizing properties. Furthermore, effective adhesion to dental surfaces is crucial. Inspired by the wet adhesion properties of the salivary acquired pellicle, we developed a multifunctional gargle named Ce6@PDN-SAP (CP-SAP). This formulation employed peptide dendrimer nanogels (PDN) as a carrier for the photosensitizer Ce6, further functionalized with saliva-acquired peptide (SAP) to confer wet adhesion properties. CP-SAP rapidly adhered to the dental surface and remained effective for extended periods. Upon laser irradiation, Ce6 generated reactive oxygen species (ROS), disrupting bacterial outer membrane integrity, causing protein leakage, and reducing ATP levels, thereby achieving potent antibacterial effects. Following this, PDN and SAP acted as nucleation templates to promote in situ remineralization of demineralized dental hard tissues. In vivo studies using rat models demonstrated that CP-SAP provided significantly superior caries-preventive effects compared to chlorhexidine gargle. In conclusion, CP-SAP, as an innovative approach grounded in the IDC theory, holds great promise for the prevention and treatment of dental caries.